Development and validation of a highly dynamic and reusable picture-based scale: A new affective measurement tool - Liu, Ping; Wang, Ya’nan; Hu, Jiang’ning; Qing, Lin’bo; Zhao, Ke (Frontiers in Psychology, 2023)
Emotion measurement is crucial to conducting emotion research. Numerous studies have extensively employed textual scales for psychological and organizational behavior research. However, emotions are transient states of organisms with relatively short duration, some insurmountable limitations of textual scales have been reported, including low reliability for single measurement or susceptibility to learning effects for multiple repeated use. In the present article, we introduce the Highly Dynamic and Reusable Picture-based Scale (HDRPS), which was randomly generated based on 3386 realistic, high-quality photographs that are divided into five categories (people, animals, plants, objects, and scenes). Affective ratings of the photographs were gathered from 14 experts and 209 professional judges. The HDRPS was validated using the Self-Assessment Manikin and the PANAS by 751 participants. With an accuracy of 89.73%, this new tool allows researchers to measure individual emotions continuously for their research. The noncommercial use of the HDRPS system can be freely accessible by request at http://syy.imagesoft.cc:8989/Pictures.7z.